BUILD-VPH Leptospira serosurvey - Alinaitwe, Lordrick; Kivali, Velma; Aturinda, Christopher; Bugeza, James; Wainaina, Martin; Richter, Martin; Hoona, Jolly; Roesel, Kristina; Mayer-Scholl, Anne; Cook, Elizabeth Anne; Kankya, Clovice; Dürr, Salome (2024)
These are datasets from a cross-sectional survey conducted in 887 cattle, 926 pigs, and 463 goats and sheep from slaughter facilities in Uganda. The files include animal demographic information (age, sex, breed, origin, study site), laboratory results (serological testing), Rscript and outputs of analyses. The laboratory test results are based on the microscopic agglutination test (MAT) that measure antibodies in serum against a set reference Leptospira serovars/serogroup. Note: Cattle were not tested since recent reports from comparable studies exist.